Successful experience through beekeeping in wind farms in the North of the Bahia State (Research, Society and Development, 2020)
The contribution that the action plan “Rational beekeeping in the area of the wind farms in Casa Nova - BA” was analyzed with the beekeepers who participated in the project. The research reports were carried out with the interaction between the beneficiaries in the form of action, reflection and theory, being characterized as action research, presenting a qualitative and quantitative character. The average number of hives populated by beekeepers was 17 ± 6 (mean ± standard deviation). The first honey harvest was carried out by nine beekeepers (52.9%), obtaining a total of 2,936 Kg of honey, with a very satisfactory hive production, being 15.27 kg ± 6.8 (mean ± standard deviation). The activity aroused the interest of beekeepers' families, mainly including the participation of young people and women. The action plan provided subsidies for the development of beekeeping, strengthening beekeeping for a source of income for families.